Nagwa uses cookies to ensure you get the best experience on our website. Learn more about our Privacy Policy.

Start Practicing

Worksheet: Differentiation of the Natural Exponential Function

Q1:

Find the first derivative of the function 𝑦 = 4 π‘₯ + 2 𝑒 6 π‘₯ .

  • A 4 π‘₯ + 2 𝑒 5 π‘₯
  • B 2 4 π‘₯ βˆ’ 2 𝑒 5 π‘₯
  • C 2 4 π‘₯ + 2 5
  • D 2 4 π‘₯ + 2 𝑒 5 π‘₯

Q2:

Differentiate the function 𝑦 = 3 𝑒 βˆ’ 5 √ π‘₯ π‘₯ 3 .

  • A 𝑦 β€² = 3 𝑒 + 5 3 π‘₯ π‘₯ 2 3
  • B 𝑦 β€² = 3 𝑒 βˆ’ 5 3 π‘₯ π‘₯ βˆ’ 4 3
  • C 𝑦 β€² = 3 𝑒 βˆ’ 5 3 π‘₯ π‘₯ 2 3
  • D 𝑦 β€² = 3 𝑒 + 5 3 π‘₯ π‘₯ βˆ’ 4 3
  • E 𝑦 β€² = 3 𝑒 + 5 3 π‘₯ 2 3

Q3:

Find the derivative of the function .

  • A
  • B
  • C
  • D
  • E

Q4:

Find the first derivative of the function 𝑦 = 𝑒 7 8 π‘₯ 5 π‘₯ t a n .

  • A βˆ’ 𝑒 ο€Ή 5 8 π‘₯ + 8 8 π‘₯  7 8 π‘₯ 5 π‘₯ 2 2 t a n s e c t a n
  • B 𝑒 ( 5 8 π‘₯ βˆ’ 8 8 π‘₯ ) 7 8 π‘₯ 5 π‘₯ 2 t a n s e c t a n
  • C 𝑒 ο€Ή 5 8 π‘₯ βˆ’ 8 8 π‘₯  7 8 π‘₯ 5 π‘₯ 2 t a n s e c t a n
  • D 𝑒 ο€Ή 5 8 π‘₯ βˆ’ 8 8 π‘₯  7 8 π‘₯ 5 π‘₯ 2 2 t a n s e c t a n
  • E 𝑒 ο€Ή 8 π‘₯ βˆ’ 8 8 π‘₯  7 8 π‘₯ 5 π‘₯ 2 2 t a n s e c t a n

Q5:

Find the derivative of the function 𝑦 = βˆ’ 4 ο€½ βˆ’ 𝑒 + 5 𝑒 + 5  c o s π‘₯ π‘₯ .

  • A 𝑦 β€² = βˆ’ 4 0 𝑒 𝑒 + 5 ο€½ βˆ’ 𝑒 + 5 𝑒 + 5  π‘₯ π‘₯ π‘₯ π‘₯ s i n
  • B 𝑦 β€² = 4 0 𝑒 ( 𝑒 + 5 ) ο€½ βˆ’ 𝑒 + 5 𝑒 + 5  π‘₯ π‘₯ 2 π‘₯ π‘₯ s i n
  • C 𝑦 β€² = 4 ο€½ βˆ’ 𝑒 + 5 𝑒 + 5  s i n π‘₯ π‘₯
  • D 𝑦 β€² = βˆ’ 4 0 𝑒 ( 𝑒 + 5 ) ο€½ βˆ’ 𝑒 + 5 𝑒 + 5  π‘₯ π‘₯ 2 π‘₯ π‘₯ s i n
  • E 𝑦 β€² = βˆ’ 4 ο€½ βˆ’ 𝑒 + 5 𝑒 + 5  s i n π‘₯ π‘₯

Q6:

Find 𝑓 β€² ( 4 ) , if 𝑓 ( π‘₯ ) = 8 𝑒 6 π‘₯ .

  • A 1 4 𝑓 ( 4 )
  • B 8 𝑓 ( 4 )
  • C 4 8 𝑓 ( 4 )
  • D 6 𝑓 ( 4 )

Q7:

If 𝑓 ( π‘₯ ) = βˆ’ 5 𝑒 βˆ’ 9 π‘₯ , find 𝑓 ( π‘₯ ) β€² .

  • A βˆ’ 1 8 𝑒 βˆ’ 9 π‘₯
  • B 𝑒 βˆ’ 9 π‘₯
  • C βˆ’ 5 𝑒 βˆ’ 1 0 π‘₯
  • D 4 5 𝑒 βˆ’ 9 π‘₯
  • E βˆ’ 5 𝑒 βˆ’ 8 π‘₯

Q8:

Find the derivative of the function 𝑦 = 5 𝑒 2 πœƒ t a n .

  • A 𝑦 β€² = 1 0 𝑒 πœƒ 2 πœƒ 2 t a n c s c
  • B 𝑦 β€² = βˆ’ 1 0 𝑒 πœƒ 2 πœƒ 2 t a n s e c
  • C 𝑦 β€² = βˆ’ 1 0 𝑒 πœƒ 2 πœƒ 2 t a n c s c
  • D 𝑦 β€² = 1 0 𝑒 πœƒ 2 πœƒ 2 t a n s e c
  • E 𝑦 β€² = 1 0 𝑒 πœƒ 2 πœƒ t a n t a n

Q9:

Differentiate 𝑓 ( π‘₯ ) = 𝑒 π‘₯ π‘₯ s e c .

  • A 𝑓 β€² ( π‘₯ ) = 𝑒 ο€Ή π‘₯ + π‘₯  π‘₯ 2 s e c t a n
  • B 𝑓 β€² ( π‘₯ ) = 𝑒 π‘₯ ( 1 βˆ’ π‘₯ ) π‘₯ s e c t a n
  • C 𝑓 β€² ( π‘₯ ) = π‘₯ ( 1 + 𝑒 π‘₯ ) s e c t a n π‘₯
  • D 𝑓 β€² ( π‘₯ ) = 𝑒 π‘₯ ( 1 + π‘₯ ) π‘₯ s e c t a n
  • E 𝑓 β€² ( π‘₯ ) = 𝑒 π‘₯ π‘₯ π‘₯ s e c t a n

Q10:

Find the first derivative of the function 𝑦 = 3 𝑒 4 7 π‘₯ s e c .

  • A 8 4 𝑒 7 π‘₯ 4 7 π‘₯ 2 s e c t a n
  • B 3 𝑒 4 7 π‘₯ s e c
  • C βˆ’ 8 4 𝑒 7 π‘₯ 7 π‘₯ 4 7 π‘₯ s e c s e c t a n
  • D 8 4 𝑒 7 π‘₯ 7 π‘₯ 4 7 π‘₯ s e c s e c t a n
  • E 1 2 𝑒 7 π‘₯ 7 π‘₯ 4 7 π‘₯ s e c s e c t a n

Q11:

Find the first derivative of the function 𝑦 = 𝑒 3 βˆ’ 4 π‘₯ βˆ’ 3 3 .

  • A βˆ’ 4 π‘₯ 𝑒 3 ( βˆ’ 4 π‘₯ βˆ’ 3 ) 1 3 3
  • B 𝑒 1 3 3 ( βˆ’ 4 π‘₯ βˆ’ 3 )
  • C βˆ’ 3 6 π‘₯ 𝑒 2 ( βˆ’ 4 π‘₯ βˆ’ 3 ) 1 3 3
  • D βˆ’ 4 π‘₯ 𝑒 2 ( βˆ’ 4 π‘₯ βˆ’ 3 ) 1 3 3

Q12:

Differentiate 𝑧 ( 𝑦 ) = 𝐴 5 𝑦 + 𝐡 𝑒 3 3 𝑦 .

  • A d d 𝑧 𝑦 = 𝐴 5 𝑦 + 𝐡 𝑒 4 3 𝑦
  • B d d 𝑧 𝑦 = βˆ’ 3 𝐴 5 𝑦 + 3 𝐡 𝑒 2 3 𝑦
  • C d d 𝑧 𝑦 = βˆ’ 3 𝐴 5 𝑦 + 3 𝐡 𝑒 3 3 𝑦
  • D d d 𝑧 𝑦 = βˆ’ 3 𝐴 5 𝑦 + 3 𝐡 𝑒 4 3 𝑦
  • E d d 𝑧 𝑦 = 𝐴 5 𝑦 + 𝐡 𝑒 2 3 𝑦

Q13:

Find the derivative of the function 𝑓 ( 𝑑 ) = ο€» 𝑒  s i n 2 5 𝑑 s i n 2 .

  • A 𝑓 β€² ( 𝑑 ) = 1 0 𝑒 ο€» 𝑒  5 𝑑 ο€» 𝑒  5 𝑑 s i n s i n s i n 2 2 2 5 𝑑 5 𝑑 5 𝑑 s i n s i n c o s c o s
  • B 𝑓 β€² ( 𝑑 ) = βˆ’ 2 0 𝑒 ο€» 𝑒  5 𝑑 ο€» 𝑒  5 𝑑 s i n s i n s i n 2 2 2 5 𝑑 5 𝑑 5 𝑑 s i n s i n c o s c o s
  • C 𝑓 β€² ( 𝑑 ) = βˆ’ 1 0 𝑒 ο€» 𝑒  5 𝑑 ο€» 𝑒  5 𝑑 s i n s i n s i n 2 2 2 5 𝑑 5 𝑑 5 𝑑 s i n s i n c o s c o s
  • D 𝑓 β€² ( 𝑑 ) = 2 0 𝑒 ο€» 𝑒  5 𝑑 ο€» 𝑒  5 𝑑 s i n s i n s i n 2 2 2 5 𝑑 5 𝑑 5 𝑑 s i n s i n c o s c o s
  • E 𝑓 β€² ( 𝑑 ) = 2 𝑒 ο€» 𝑒  ο€» 𝑒  s i n s i n s i n 2 2 2 5 𝑑 5 𝑑 5 𝑑 s i n c o s

Q14:

Find the derivative of the function 𝑓 ( 𝑧 ) = βˆ’ 3 𝑒 4 𝑧 4 𝑧 + 1 .

  • A 𝑓 β€² ( 𝑧 ) = βˆ’ 3 𝑒 ( 4 𝑧 + 1 ) 4 𝑧 4 𝑧 + 1 2
  • B 𝑓 β€² ( 𝑧 ) = βˆ’ 1 2 𝑒 4 𝑧 + 1 4 𝑧 4 𝑧 + 1
  • C 𝑓 β€² ( 𝑧 ) = 1 2 𝑒 ( 4 𝑧 + 1 ) 4 𝑧 4 𝑧 + 1 2
  • D 𝑓 β€² ( 𝑧 ) = βˆ’ 1 2 𝑒 ( 4 𝑧 + 1 ) 4 𝑧 4 𝑧 + 1 2
  • E 𝑓 β€² ( 𝑧 ) = 3 𝑒 ( 4 𝑧 + 1 ) 4 𝑧 4 𝑧 + 1 2

Q15:

Find the first derivative of the function 𝑦 = 4 𝑒 7 π‘₯ + 4 7 π‘₯ .

  • A βˆ’ 2 8 π‘₯ 𝑒 + 8 4 𝑒 ( 7 π‘₯ + 4 ) 7 π‘₯ 7 π‘₯ 2
  • B βˆ’ 1 9 6 π‘₯ 𝑒 + 8 4 𝑒 ( 7 π‘₯ + 4 ) 7 π‘₯ 7 π‘₯ 2
  • C 1 9 6 π‘₯ 𝑒 + 8 4 𝑒 7 π‘₯ + 4 7 π‘₯ 7 π‘₯
  • D 1 9 6 π‘₯ 𝑒 + 8 4 𝑒 ( 7 π‘₯ + 4 ) 7 π‘₯ 7 π‘₯ 2
  • E 1 9 6 𝑒 + 8 4 𝑒 ( 7 π‘₯ + 4 ) 7 π‘₯ 7 π‘₯ 2

Q16:

Find the first derivative of the function 𝑦 = ο€Ή 2 𝑒 βˆ’ 5 𝑒  4 π‘₯ βˆ’ 5 π‘₯ 4 .

  • A 4 ο€Ή 2 𝑒 βˆ’ 5 𝑒  4 π‘₯ βˆ’ 5 π‘₯ 4
  • B ο€Ή 2 𝑒 βˆ’ 5 𝑒  ο€Ή 8 𝑒 + 2 5 𝑒  4 π‘₯ βˆ’ 5 π‘₯ 3 4 π‘₯ βˆ’ 5 π‘₯
  • C βˆ’ 4 ο€Ή 2 𝑒 βˆ’ 5 𝑒  ο€Ή 8 𝑒 + 2 5 𝑒  4 π‘₯ βˆ’ 5 π‘₯ 3 4 π‘₯ βˆ’ 5 π‘₯
  • D 4 ο€Ή 2 𝑒 βˆ’ 5 𝑒  ο€Ή 8 𝑒 + 2 5 𝑒  4 π‘₯ βˆ’ 5 π‘₯ 3 4 π‘₯ βˆ’ 5 π‘₯
  • E 4 ο€Ή 2 𝑒 βˆ’ 5 𝑒  ο€Ή 8 𝑒 + 2 5 𝑒  4 π‘₯ βˆ’ 5 π‘₯ 4 4 π‘₯ βˆ’ 5 π‘₯

Q17:

Find the derivative of the function .

  • A
  • B
  • C
  • D
  • E

Q18:

Differentiate β„Ž ( 𝑑 ) = 5 √ 𝑑 βˆ’ 𝑒 3 𝑑 .

  • A β„Ž β€² ( 𝑑 ) = 5 3 √ 𝑑 βˆ’ 𝑒 3 𝑑
  • B β„Ž β€² ( 𝑑 ) = 5 √ 𝑑 βˆ’ 𝑒 3 2 𝑑
  • C β„Ž β€² ( 𝑑 ) = 5 3 √ 𝑑 βˆ’ 𝑒 3 4 𝑑
  • D β„Ž β€² ( 𝑑 ) = 5 3 √ 𝑑 βˆ’ 𝑒 3 2 𝑑
  • E β„Ž β€² ( 𝑑 ) = 5 3 √ 𝑑 βˆ’ 𝑒 3 2 𝑑

Q19:

Differentiate β„Ž ( 𝑑 ) = √ 𝑑 βˆ’ 3 𝑒 5 4 𝑑 .

  • A β„Ž β€² ( 𝑑 ) = 1 5 √ 𝑑 βˆ’ 1 2 𝑒 5 4 𝑑
  • B β„Ž β€² ( 𝑑 ) = 1 √ 𝑑 βˆ’ 3 𝑒 5 4 4 𝑑
  • C β„Ž β€² ( 𝑑 ) = 1 5 √ 𝑑 βˆ’ 1 2 𝑒 5 6 4 𝑑
  • D β„Ž β€² ( 𝑑 ) = 1 5 √ 𝑑 βˆ’ 1 2 𝑒 5 4 4 𝑑
  • E β„Ž β€² ( 𝑑 ) = 1 5 √ 𝑑 βˆ’ 3 𝑒 5 4 4 𝑑

Q20:

Determine the derivative of 𝑔 ( π‘₯ ) = βˆ’ 5 𝑒 βˆ’ 3 π‘₯ + 3 π‘₯ 2 .

  • A 𝑔 β€² ( π‘₯ ) = βˆ’ 5 𝑒 βˆ’ 3 π‘₯ + 3 π‘₯ 2
  • B 𝑔 β€² ( π‘₯ ) = 𝑒 ο€Ή 1 5 π‘₯ βˆ’ 1 5 π‘₯  βˆ’ 3 π‘₯ + 3 π‘₯ 2 2
  • C 𝑔 β€² ( π‘₯ ) = 𝑒 ο€Ή 3 0 π‘₯ βˆ’ 1 5  βˆ’ 3 π‘₯ + 3 π‘₯ 2 2
  • D 𝑔 β€² ( π‘₯ ) = 𝑒 ( 3 0 π‘₯ βˆ’ 1 5 ) βˆ’ 3 π‘₯ + 3 π‘₯ 2
  • E 𝑔 β€² ( π‘₯ ) = 5 𝑒 βˆ’ 3 π‘₯ + 3 π‘₯ 2